The transverse hall effect in a quantum well with high infinite potential in the influence of confined optical phonons - Hung, Le Thai; Bau, Nguyen Quang; Thang, Pham Ngoc (VNU Journal of Science: Mathematics - Physics, 2017)
Abstract. The Transverse Hall effect ( THE ) has been theoretical studied in a quantum well ( QW ) with high infinite potential subjected to a crossed dc electric field and a magnetic field ( MF ) which is oriented perpendicularly to the confinement direction in the present of an intense electromagnetic wave ( EMW ). The analytical expression of the transverse hall coefficient ( THC ) which depends not only on the parameters of the system but especially on the quantum number m characterizing confined phonons, is obtained by using the quantum kinetic equation method for confined electrons - confined optical phonons interaction. The analytic expression of THC is numerically evaluated, plotted and discussed for a specific case of the AlAs/GaAs/AlAs QW . Results show the THC depends strong nonlinearly on the EMW amplitude and the MF. All results are compared with that in case of unconfined phonons to see differences.